Trocas gasosas na cultura do feijão Caupi sob aplicações de bokashi - Lima, Gabriela Torres Costa. (2019)
One of the main causes of loss stored grain is the pests' attack which undertakes the quality and discards the using for planting, causing large losses to farmers. The main bisects considered harmful to grain beans are Callosobruchus maculatus and Acaniharcelides obtectus species. The aim of this study was to evaluate the essential oils bioactivity from fennel plants Foeniculum vulgare, citronella grass Cymbopogon winterianta and crude oils neem Azadirachia indica and moringa Moringa oinfente against the mortality and preference of adult insects A. obtectus and C. maculatus. The experiments were conducted at the Entomology Laboratory, Department of AgricultureCCHSA/UFPB. In the experimental procedure we used two methodologies: No-choice (fumigation) and free-choice. The no-choice method was performed in plastic containers with 250 ml capacity. The interior was lined with filter paper impregnated with oil at doses of 5, 10, 15, 20, 30, 40 and 50 p1/0.251., of air, and a control. Twenty insects were released on disc and evaluation was conducted 24 hours after the submission of tested insects. In the free-choice test were used arenas formed with five plastic boxes, with central box connected symmetrically. Samples of 30g of cowpea were impregnated with vegetable oils at doses of 5, 10, 15 and 20 p.1 and control. Grains treated with oils were placed in symmetrically opposite boxes and grains not treated in the other two boxes. Fifty insects were released in the center box and after 24 hours were counted the number of live insects in each box. From the data obtained from the tests, no-choice and free choice effectiveness and Preference Index were calculated, respectively. Completely randomized design was used in a factorial in both tests. For ANOVA and regression analysis it was used the GLM procedure of SAS. Results of no-choice test (Fumigation) showed efficacy for fennel oil of 91.83%, 97.95% and 100% for doses of 30, 40 and 50 m1/0.25L of air. For the same doses with citronella oil, there was a efficacy of 58%, 69% and 80.43% for A. obtectus. For C. maculatus the effectiveness of aforementioned doses were 90.81%, 86.73% and 81.63% for fennel and 76.04%, 71.87% and 73.95% for citronella grass oils. It was also found that there was a decrease in the ratio of live insects when those doses were increased. In the test free choice, it was found that the fennel oil and moringa were the most attractive compared to oils of citronella and neem. For the result of the repellency of live insects C. maculates to vegetable oils found out there was no significant difference between the oils. However it was found that citronella oil was better than the others by having repellency at all doses applied. The results obtained for the preference index has been observed that the doses applied to the repellents citronella oil were to C. rnaculatus adults.